Overview and Reinstatement of Some Geophysical Interpretations in the Eastern Sava Depression (Rudarsko-geološko-naftni zbornik, 2022)
The eastern part of Sava Depression is bounded on the south with the Sava River and on the north with Psunj Mountain,Požeška and Dilj Hills. In this part thicker Neogene-Quaternary sediments than in the western part were found, and thereis almost never reached thermal maturity sufficient to catagenesis. Therefore, after the first seismic survey and exploratorydrilling, a new additional research never continued. The overview and assessment of the reconstruction of the part ofgeophysical measurements was prepared in the eastern part of the Sava Depression. In some previous interpretations rocksbetween the Upper Pannonian and Upper Pontian are described as result of deltaic systems, with the clinoforms. Regionaldeposition at the time of the Early Pannonian indicates the beginning of significant changes in the environment in Croatianpart of the Pannonian Basin System (CPBS), with a distinct domination of turbidites. Clinoforms are possible results ofespecially psammitic detritus deposited toward the margins of the depression, and partly in the direction materialtransport. In the Early Pontian regionally depositional environments started to be local. In the Quaternary can be expectedthe existence of the delta or alluvial fans.